Karakteristik Nugget Ikan Kombinasi Cakalang (Katsuwonus pelamis) dan Wortel (Daucus carrota L.) - Maitale, Maria; Moniharapon, Erynola; Mailoa, Meitycorfrida (Universitas Pattimura, 2024)
Skipjack Nuggets are a seafood alternative to traditional chicken nuggets. This research aims to determine the appropriate carrot concentration to obtain the nuggets' best chemical and sensory characteristics. The research results on Skipjack Nugget treated with a carrot concentration of 100g is the right concentration to produce a nugget with good chemical characteristics. Characteristics of skipjack nuggets with a carrot concentration of 100 g have 34.32% moisture content, 40.65% fiber content, 17.47% fat content, and 13,73% protein content.